Comparison of Once- with Twice-Daily Dosing of Fluticasone Propionate in Mild and Moderate Asthma - Louis-Philippe Boulet; Robert L Cowie; Roberto Dal Negro; Wade Brett; Milton Gold; Agostinho Marques; William S Thorburn; Nate M Stepner; Reid Bobson (Canadian Respiratory Journal)
OBJECTIVES: Two 12-week, randomized, double-blind, parallel-group studies were performed to compare the efficacy and safety of once- and twice-daily dosing of fluticasone propionate (FP) in the treatment of mild to moderate asthma, considered to require the equivalent of either 200 or 500 µg of FP daily.